Innovations politiques et participation autochtone : les ambivalences de la mise en œuvre de la convention nº 169 de l’OIT sur les peuples indigènes au Chili - Matilde Spoerer (L'Ordinaire des Amériques)
This article critically examines the way in which the innovations concerning indigenous participation have been unilaterally presented as factors of democratization. From the study of the implementation of convention n° 169 of the International Labor Organization (ILO) on the rights of autochthonous peoples in Chile, the article calls for a more complex consideration of the topic by highlighting the mechanisms of re-appropriation of this tool and the various types of interactions between indigenous and state actors in the framework of indigenous consultations. Finally, the article shows that the indigenous participation devices introduce ambivalent changes in the power relationships.